2013 IEEE International Conference on Control System, Computing and Engineering 2013
DOI: 10.1109/iccsce.2013.6719972
|View full text |Cite
|
Sign up to set email alerts
|

Application of virtual windows to determine the path of a uniformly moving obstacle

Abstract: -Two virtual windows are used to determine the path of a single uniformly moving obstacle. If the path of the obstacle crosses the two virtual windows, then its path can be easily determined. A few simulations were implemented to ascertain the viability and effectiveness of this technique. A table with recommended maximum speed of the uniformly moving obstacle was also provided, given the specified pixel resolution and gap between the virtual windows.Index Terms -virtual window, uniformly moving obstacle, path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The research work that is reported here is based on reactive approach utilising virtual window. This is an extension and improvement of a previous work described in [16]. Unlike [17][18], the technique implemented can be used to determine the path and speed of a moving obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…The research work that is reported here is based on reactive approach utilising virtual window. This is an extension and improvement of a previous work described in [16]. Unlike [17][18], the technique implemented can be used to determine the path and speed of a moving obstacle.…”
Section: Introductionmentioning
confidence: 99%